(untitled) - Kinicki, Angelo (New York, 2008)
Our primary goal is simple to state but hard to execute: to make learning principles of management as easy, efficient, and effective as possible. Accordingly, the book intergrates writing , illustration, design, and manazine-like layout in a program of learning that appeals to the visual sensibilities and respects the time constraints and different learning styles of today's student.
Keywords: Manegement,Practical management,Quản lí,Quản lý trong thực tế; United States,United States,Hoa Kỳ,Hoa Kỳ